2020
DOI: 10.1002/smll.202003357
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ultrahigh‐Quality Monolayer Molybdenum Disulfide through In Situ Defect Healing with Thiol Molecules

Abstract: Monolayer transition metal dichalcogenides are 2D materials with many potential applications. Chemical vapor deposition (CVD) is a promising method to synthesize these materials. However, CVD‐grown materials generally have poorer quality than mechanically exfoliated ones and contain more defects due to the difficulties in controlling precursors' distribution and concentration during growth where solid precursors are used. Here, thiol is proposed to be used as a liquid precursor for CVD growth of high quality a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 65 publications
1
44
0
Order By: Relevance
“…Curve 2 in Figure 4 d shows the Raman spectrum obtained from the substrate at point 2. The PL spectrum (Curve 1) of monolayer MoS 2 shows a strong peak at 1.84 eV ( Figure 4 e), which is consistent with the A exciton peak due to the direct bandgap of monolayer MoS 2 [ 19 , 47 ]. Curve 2 in Figure 4 e is the PL spectrum obtained from the substrate at point 2.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Curve 2 in Figure 4 d shows the Raman spectrum obtained from the substrate at point 2. The PL spectrum (Curve 1) of monolayer MoS 2 shows a strong peak at 1.84 eV ( Figure 4 e), which is consistent with the A exciton peak due to the direct bandgap of monolayer MoS 2 [ 19 , 47 ]. Curve 2 in Figure 4 e is the PL spectrum obtained from the substrate at point 2.…”
Section: Resultssupporting
confidence: 60%
“…The Raman spectrum of monolayer MoS 2 shows that the frequency difference between the E 1 2g mode located at 382 cm −1 and the A 1g mode located at 403 cm −1 was approximately 21 cm −1 ( Figure 1 i), which is consistent with that of the reported monolayer MoS 2 [ 31 ]. Due to the direct bandgap of monolayer MoS 2 , the PL spectrum of MoS 2 shows a strong A exciton peak at 1.84 eV ( Figure 1 j) [ 19 , 47 ]. Raman and PL maps show that monolayer MoS 2 exhibited nonuniform Raman and PL peak intensities, confirming that monolayer MoS 2 had nonuniform optical and electronic properties ( Figure 1 k–m).…”
Section: Resultsmentioning
confidence: 99%
“…have developed an elegant in situ thiol molecule assisted CVD approach and the as‐grown monolayer MoS 2 have the lowest sulfur vacancy concentration among CVD samples. [ 13 ] Here, the poly(3,4‐ethylenedioxythiophene):poly(4‐styrenesulfonate) (PEDOT:PSS)‐induced selenium (Se) vacancy healing effect was employed to significantly reduce the Se vacancy density of the WSe 2 flakes (Experimental Section). Generally, widespread Se vacancies in CVD‐grown WSe 2 flakes are considered to function as electron doping, [ 11b,14 ] suggesting reducing Se vacancies can increase the hole density.…”
Section: Resultsmentioning
confidence: 99%
“…To minimize the density of these sulphur vacancies, our LCVD method used C12H25SH as precursor, which not only provided a continuous sulphur precursor but also in-situ repaired the sulphur vacancies during CVD growth. 9 In this way, we obtained MoS2 samples with the lowest density of sulphur vacancies (0.32 nm -2 ) among all CVD samples reported so far, as revealed by high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) and the corresponding simulation result (Figures 6e and 6f). And the optical quality of the LCVD-grown MoS2 was checked using PL measurements at low temperature (80 K) and showed that the full width at half maximum was 44 meV, which was closed to that of the exfoliated MoS2 (Figure 6g).…”
Section: Improving Materials Qualitymentioning
confidence: 65%